Предмет: Алгебра,
автор: MadDanil22
ПОМОГИТЕ ПОЖАЛУЙСТА СРОЧНО ПРОШУ
Приложения:
Ответы
Автор ответа:
1
7) а)
б)
4)
2ab*(3a^2 - 2b^2) - 3ab*(4b^2 - a^2) = 6a^3b - 4ab^3 - 12ab^3 + 3a^3b = 9a^3b - 16ab^3 = ab(9a^2 - 16b^2) = ab*(3a - 4b)*(3a + 4b) = -2*(3 + 8)*(3 - 8) = -2*11*(-5) = 110
Ответ: 110
б)
4)
2ab*(3a^2 - 2b^2) - 3ab*(4b^2 - a^2) = 6a^3b - 4ab^3 - 12ab^3 + 3a^3b = 9a^3b - 16ab^3 = ab(9a^2 - 16b^2) = ab*(3a - 4b)*(3a + 4b) = -2*(3 + 8)*(3 - 8) = -2*11*(-5) = 110
Ответ: 110
Похожие вопросы
Предмет: Физика,
автор: cgvdhbdyv
Предмет: Биология,
автор: kkbeka70
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Swaggafox04
Предмет: Геометрия,
автор: 89851136781